Does the open shop harm union collective action?. Issue 2 (15th March 2021) - Zullo, Roland
Abstract: In the United States, right‐to‐work (RTW) laws impose the open shop on labour unions. I test whether RTW affects the frequency and outcomes of union representation petitions. Quasi‐experimental tests reveal no association between RTW law and the volume of certification petitions filed and that fewer certification petitions are withdrawn under RTW. Thus, unions do not appear to retreat from new member organizing under RTW law. Moreover, RTW correlates with a decline in decertification and unit clarification petitions, implying that under the open shop, RTW law reduces internal union dissension. Although fewer decertification cases go to an election under RTW law, unions are more likely to lose cases that proceed to a referendum. These changes benefit smaller more than larger bargaining units. I infer that the law nudges the system away from an industrial union model in favour of smaller, craft or occupation‐based units.